Navigating Career Paths in a Foreign Land : A Focus on Determinants of Career Choices among Educated Immigrants and International Students in Jyväskylä - Behm, Thiranga (2024)
The study examines the variables that affect the employment decisions of educated immigrants and international students in Jyväskylä, Finland. Qualitative methodology was used and 10 educated immigrants and international students were interviewed in winter, 2023. The study poses the following research questions: What elements did the participants interviewed for this study (i.e. educated immigrants and international students) perceive to affect their choice of career in Finland? and To what extent did the participants interviewed for this study explain their career decision making process in Finland to be influenced by cultural differences and language barriers?. Thematic analysis was used and themes such as language barriers, cultural differences, resilience, and adaptability have been identified in the research. These findings emphasise the interaction between structural obstacles and individual objectives. The results underline the importance of professional networks and integration programmes, as well as the need for legislative initiatives aimed at supporting career development by educated migrants and international students. Overall, this research has improved knowledge of the career paths of educated immigrants in Finland and the factors that influence their career choices. In addition, it provides useful data to legislators, businesses and educational institutions in order to increase the success of this population as well as its integration into the workforce.